Angiogenin in age-related macular degeneration - Skeie, Jessica M. (Molecular Vision, 2011)
PURPOSE: Age-related macular degeneration (AMD) is a common blinding disease in the elderly population. AMD is frequently complicated by choroidal neovascularization, causing irreversible losses in visual acuity. Proteins that induce pathologic angiogenesis in other systems include angiogenin, a small protein involved in angiogenesis in tumor metastases. Our goal was to determine if angiogenin participates in angiogenesis during choroidal neovascular membrane formation in AMD. METHODS: The expression of angiogenin in the human retina and retinal pigment epithelium (RPE)-choroid was determined using reverse-transcription (RT)-PCR and immunoblotting. Localization of angiogenin in human control eyes and in eyes with choroidal neovascularization was determined using immunohistochemistry. Potential angiogenin-mediated effects on endothelial cell migration, as well as angiogenin internalization by Rf/6a cells, were determined. RESULTS: Angiogenin was synthesized by the human choroid and retina and localized to normal and pathologic vasculature. Angiogenin did not change the migratory behavior of Rf/6a chorioretinal endothelial cells; however, these cells did internalize exogenous angiogenin in culture. CONCLUSIONS: Chorioretinal endothelial cells bind and internalize angiogenin, a protein localized to the choroid in normal eyes, as well as in some drusen and in neovascular membranes in AMD eyes. Angiogenin has been shown to participate in angiogenesis in other tissues. Although angiogenin does not increase the migratory behavior of these cells, it may play a role in other aspects of endothelial cell activation in neovascular AMD.